(untitled) (Brazilian Journal of Oceanography, 2011)
Despite the high number of studies on fish assemblages associated with artificial reefs and offshore platforms, little information exists on the growth rates of fish living on artificial and natural substrates. Age and growth was determined throughout otolith reading on two commercial scorpionfishes (Scorpaena porcus and Scorpaena notata) caught in the surroundings of artificial structures (artificial reefs and gas platforms) and natural habitats. Von Bertalanffy growth parameters were calculated for each species separately for each site. Age of S. porcus and S. notata ranged from 0 to 8 years and from 0 to 16 years, respectively. Kimura test applied to Von Bertalanffy growth curves indicated that the individuals of both species inhabiting the artificial structures had higher growth parameters than those caught in the natural habitat. The presence of artificial habitats in the northern Adriatic Sea positively affects growth rates and growth performance of both species, likely for the greater prey availability in respect to the natural open sea.